Ketiadaan Perlindungan Hukum Bagi Pekerja Yang Tidak Diikutkan Program Pensiun Dalam UU Cipta Kerja - Faiqah Nur Azizah; Erza Tania Dewanti; Syahrir Syahrir (ADALAH, 2022)
One of the goals of Job Creation is to achieve economic equity through ease of doing business. However, the existence of the Job Creation Law has actually added new problems, especially regarding legal protection for workers who are not included in the pension program. This is due to the imposition of sanctions, both imprisonment and fines to corporations that do not provide severance pay. For workers who are not included in the pension program, it is abolished by the Copyright Law. Therefore, the State must be present to provide legal protection and guarantee the fulfillment of rights for workers/laborers through the establishment of laws and regulations that favor the lower classes of society.